Perancangan UI/UX website e-commerce Uppervista menggunakan metode Design Thinking - Prasetio, Nanda Wiryawan; Manongga, Daniel H.F. (AITI, 2025)
The growth of innovation and rapidly growing global web penetration has had a significant impact on the business world, Uppervista Shoes Treatment which is one of the MSMEs engaged in shoe washing services. In running the business, Uppervista Shoes Treatment already has a website but has problems not functioning properly. This research discusses the UI/UX e-commerce website design as a means of promoting and selling shoe care products to expand the scope of Uppervista's business. Using the design thinking method in designing the UI/UX of the Uppervista website can help find solutions based on user obstacles as the target audience using the website. The UI/UX design of the Uppervista website was evaluated using system usability scale (SUS) testing with a score of 82.08 indicating excellent user usability and it was found that the design thinking method can solve user obstacles so far and provided convenience and comfort in finding information on the Uppervista Shoes Treatment website.